Caracterizações da compactificação de Poincaré de campos polinomiais do plano - Carrocine, Roberta Camelucci (Universidade Federal de São Carlos, 2007)
In this work, we describe the Poincaré Compactification of polinomial vector fields and present two characterization of it.
Keywords: Campos vetoriais; Análise matemática; Campos polinomiais; Mathematical analysis; Vector fields; Polinomial vector fields; CIENCIAS EXATAS E DA TERRA::MATEMATICA